PENGEMBANGAN MULTIMEDIA INTERAKTIF MATA PELAJARAN MEMBUAT POLA KELAS TATA BUSANA SMK NEGERI 1 LAGUBOTI - Ampera, Dina; Nurhayati, Nurhayati (Universitas Negeri Medan, 2019)
ABSTRACTThis research was conducted at SMK Negeri 1 Laguboti, when the research was conducted in the odd semester of the 2017-2018 academic year. The subjects of this study were students of class XI TB I at SMK Negeri 1 Laguboti on subjects making adult female patterns with 32 students. At this stage it was concluded that interactive multimedia-based learning media that were developed were effectively used in subjects making the XI Class dress pattern at SMK Negeri 1 Laguboti. Based on the results of student responses on effectiveness testing conducted at the field trial stage obtained an assessment with the criteria of